Neurocirugía en época de COVID-19. Protocolo de actuación - Massa, Daniela; Ajler, Pablo; Idarraga, Esteban; Plou, Pedro; Hem, Santiago; Landriel, Federico; Tramontano, Julián; Ciraolo, Carlos; Baccanelli, Mateo; Yampolsky, Claudio (Revista Argentina de Neurocirugía, 2020)
.